Analysis Of Accounting Information System In Atm Transaction Process At Pt Bank Rakyat Indonesia (Persero) - Sarda, Sultan; Masrullah, Masrullah; Putra, Anastasia Eka; Anggraeni, Reski (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
This study aims to determine the Role of Accounting Information Systems in the ATM Transaction Process at PT. Bank Rakyat Indonesia Makassar Branch Mangasa Unit. This research was conducted at BRI tbk Mangasa Unit from December 2020 to January 2021. The analytical method used is descriptive qualitative. The results of the study indicate that the transaction accounting information system at ATM machines is supported by an information system that uses technological sophistication in an effort to reduce errors and supervision in the use of accounting information systems on ATM machines